Physical exercise among participants in the Dialysis Outcomes and Practice Patterns Study (DOPPS): correlates and associated outcomes - Tentori, Francesca; Elder, Stacey J.; Thumma, Jyothi; Pisoni, Ronald L.; Bommer, Jürgen; Fissell, Rachel B.; Fukuhara, Shunichi; Jadoul, Michel; Keen, Marcia L.; Saran, Rajiv; Ramirez, Sylvia P. B.; Robinson, Bruce M. (Nephrology, dialysis, transplantation, 2010)
Background. Levels of physical exercise among haemodialysis patients are low. Increased physical activity in this population has been associated with improved health-related quality of life (HRQoL) and survival. However, results of previous studies may not be applicable to the haemodialysis population as a whole. The present study provides the first description of international patterns of exercise frequency and its association with exercise programmes and clinical outcomes among participants in the Dialysis Outcomes and Practice Patterns Study (DOPPS).Methods. Data from a cross section of 20 920 DOPPS participants in 12 countries between 1996 and 2004 were analysed. Regular exercise was defined as exercise frequency equal to or more than once/week based on patient self-report. Linear mixed models and logistic regression assessed associations of exercise frequency with HRQoL and other psychosocial variables. Mortality risk was calculated in Cox proportional hazard models using patient-level (patient self-reported exercise frequency) and facility-level (the dialysis facility percentage of regular exercisers) predictors.Results. Regular exercise frequency varied widely across countries and across dialysis facilities within a country. Overall, 47.4% of participants were categorized as regular exercisers. The odds of regular exercise was 38% higher for patients from facilities offering exercise programmes (adjusted odds ratio = 1.38 [95% confidence interval: 1.03-1.84]; P = 0.03). Regular exercisers had higher HRQoL, physical functioning and sleep quality scores; reported fewer limitations in physical activities; and were less bothered by bodily pain or lack of appetite (P ≤ 0.0001 for all). Regular exercise was also correlated with more positive patient affect and fewer depressive symptoms (P ≤ 0.0001). In models extensively adjusted for demographics, comorbidities and socio-economic indicators, mortality risk was lower among regular exercisers (hazard ratio = 0.73 [0.69-0.78]; P < 0.0001) and at facilities with more regular exercisers (0.92 [0.89-0.94]; P < 0.0001 per 10% more regular exercisers).Conclusions. Results from an international study of haemodialysis patients indicate that regular exercise is associated with better outcomes in this population and that patients at facilities offering exercise programmes have higher odds of exercising. Dialysis facility efforts to increase patient physical activity may be beneficial.
Gesehen am 26.10.2023